Silica/Polyimide Mixed Matrix Membrane for CO2/CH4 and O2/N2 Gas Separation : A Computational Approach - Liew, Xiau Jia; Serene Lock, Sow Mun; Mehtab, Ali Darban; Suhaib Umer, Ilyas; Lim, Lam Ghai; Yiin, Chung Loong; Irene Lock, Sow Mei; Bridgid Chin, Lai Fui (John Wiley & Sons, Inc, 2025)
Silica-incorporated polyimide (PI)-based mixed matrix membranes (MMMs) are emerging as promising candidates for gas separation. However, experimental evaluation of their performance is challenging due to the complex interactions between polymers and fillers and limitations in isolating individual transport mechanisms. This study employs Monte Carlo and molecular dynamics (MD) simulations to investigate the solubility and diffusivity of CO2/CH4 and O2/N2 in silica/6FDA-ODA PI MMMs with varying silica loadings (0–20 wt%). The mixed gas compositions are chosen to reflect real-world conditions, as 30% CO2 in CO2/CH4 mixtures, representative of sour gas in natural reserves, and 21% O2 in O2/N2 mixtures, mimicking air composition. Results indicate that incorporating 10 wt% silica enhances CO2 permeability by 270% and CO2/CH4 selectivity by 136% compared to pristine 6FDA-ODA PI. For O2/N2 separation, an O2 permeability of 23.59 and selectivity of 3.11 were achieved. These findings align well with the experimental literature, with 0.01%–10.4% deviation. Benchmarking confirms superior permeability over reported membranes, highlighting the potential of silica/6FDA-ODA PI MMMs for efficient gas separation. This study provides valuable molecular-level insights, paving the way for the rational design of high-performance membranes for industrial applications.